AIDS and its impact on the assumption and removal of public service Contribute to the re-engineering conditions of public service - المخزومي, وليد مرزة (Journal of Legal Sciences, 2019)
The research represents a contribution to the re-engineering of the conditions of the assignment of the public service and isolation of them due to illness, especially the disease, which was not treated by the law of AIDS to ensure the transfer of the person who enjoys the best physical and psychological health.